Utilization pattern and associated factors of maternal health care services in Haryana, India: a study based on district level household survey data - Ray, Shinjini; Bhandari, Pravat; Prasad, Jang Bahadur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Maternal health was one of the most important millennium development goals (MDGs), India didn’t achieve by the year 2015. Since, India is a multicultural, social and multiregional country, where some of the regions have good social and demographic achievement while some are poor. Haryana is one of them, which has 146 maternal mortality ratio. The level of receiving antenatal care (ANC) in Haryana is quite low as compared to other states of India. Objective of present study was to Understand the extent of use of maternal health care services in Haryana as well as examining the role of antenatal care and other socio-economic factors on the utilization of maternal health services. Methods: Bivariate analysis, chi-square test, and binary logistic regression have been used based on district level household and facility survey-4 data. Results: The utilization of ANC (any and full), institutional delivery and post-delivery treatment seeking varies among women by literacy, age at first marriage, age at women and place of residence. Literate women are two times more likely to access ANC [odds ratio (OR)=1.97 (any ANC), 1.95 (full ANC), p<0.01] and 1.52 times more likely to prefer institutional delivery [OR=1.52, p<0.01]. Conclusions: Empowering women through the encouragement of mother’s education should be one of the most fundamental strategies to promote maternal health care services and reduce inequalities.